Application of resilience theories in the transition to parenthood: a scoping review. (15th March 2019) - Young, Cecily; Roberts, Rachel; Ward, Lynn
ABSTRACT: Objective : Investigate the use of resilience theories in the transition to parenthood literature. Background : The transition to parenthood is a key developmental experience for many adults. Resilience is a unifying theoretical concept which incorporates many of the skills and resources linked with the transition to parenthood, but the uptake of resilience theory in this literature is unknown. Methods : We used a scoping review to examine the use of resilience theory in published transition to parenthood research. This included a systematic search of the literature, descriptive analysis of theories and methods used and an assessment of theoretical integration. Results : We identified 17 studies which met inclusion criteria. Explicit use of theory occurred in six studies and quality of theoretical integration was high for all of these. Resilience was seen as a desirable concept for mapping complex data, taking a holistic approach to psychological health and acknowledging environmental and systemic influences. We also identified 29 resilience supporting factors including positive self-concept, optimism, social support, family relationships, community services and social connectedness. Conclusion : Resilience is a useful concept for synthesising information about the transition to parenthood.